Digital human modeling. applications in health, safety, ergonomics and risk management : 6th International Conference, DHM 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings /: applications in health, safety, ergonomics and risk management : 6th International Conference, DHM 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings. Human modeling : Part I, (2015) - Unknown
No abstract available